28.3k views
2 votes
(7x+5)(2x^3-4x^2+9x-3)

User Ayoub
by
5.4k points

1 Answer

4 votes

Answer:


\large\boxed{(7x+5)(2x^3-4x^2+9x-3)=14x^4-18x^3+43x^2+24x-15}

Explanation:

Use FOIL: (a + b)(c + d) = ac + ad + bc + bd


(7x+5)(2x^3-4x^2+9x-3)\\\\=(7x)(2x^3)+(7x)(-4x^2)+(7x)(9x)+(7x)(-3)\\+(5)(2x^3)+(5)(-4x^2)+(5)(9x)+(5)(-3)\\\\=14x^4-28x^3+63x^2-21x+10x^3-20x^2+45x-15\\\\\text{combine like terms}\\\\=14x^4+(-28x^3+10x^3)+(63x^2-20x^2)+(-21x+45x)-15\\\\=14x^4-18x^3+43x^2+24x-15

User Beau Crawford
by
6.1k points